The Advances of Neutrophil-Derived Effective Drug Delivery Systems: A Key Review of Managing Tumors and Inflammation - Wang H (Dove Medical Press, 2021)
Huaiji Wang,1 Jie Zang,2 Zihan Zhao,3 Qin Zhang,1 Shunjie Chen1 1Department of Nephrology, Shanghai Fourth People’s Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of China; 2The Institute for Biomedical Engineering & Nano Science, School of Medicine, Tongji University, Shanghai, People’s Republic of China; 3Department of Dermatology, Shanghai Tenth People’s Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of ChinaCorrespondence: Shunjie ChenDepartment of Nephrology, Shanghai Fourth People’s Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of ChinaEmail chenshunjie77csj@163.comAbstract: The chimeric trait of recruitment by inflammatory signals endows neutrophils with the functionality of migrating to inflamed tissues, which can be utilized to tailor novel drug delivery systems. In this review, we introduce a mechanism of neutrophil-derived drug delivery systems recruited into inflamed sites and provide insight into tumors and inflammation therapy. In particular, the advantages of neutrophils—their endogenous-derived neutrophil membrane, exosomes as drug carriers for augmented targeting, prolonged circulation, and improved biostability—were concluded. Subsequently, the latest application in the treatment of tumors and inflammation was elaborated upon, followed by a discussion of the future prospects to neutrophil-derived delivery systems. This promising system will provide new therapeutic avenues for the treatment of inflammation and tumors.Keywords: neutrophil-derived delivery, tumors and inflammation, targeting, circulation, biostability